Rapid granulation using calcium sulfate and polymers for refractory wastewater treatment in up-flow anaerobic sludge blanket reactor. (June 2020) - Liang, Jiahao; Wang, Qinghong; Yoza, Brandon A.; Li, Qing X.; Chen, Chunmao; Ming, Jie; Yu, Jingshi; Li, Jin; Ke, Ming
Graphical abstract: Highlights: CaSO4 /GG and CaSO4 /CPAM were novel used in UASB reactors. The CaSO4 together with polymers accelerated anaerobic sludge granulation. The dissolution of CaSO4 improved granules size and methanogenic activity. Phenols degraders enriched in reactors containing CaSO4 and polymers. Combined CaSO4 with polymers improved UASB performance. Abstract: Long start-up period and slow granulation are major restraints in up-flow anaerobic sludge blanket (UASB) reactors for the treatment of refractory wastewater. In this study, Calcium sulfate (CaSO4 ), CaSO4 /guar gum (GG), and CaSO4 /cationic polyacrylamide (CPAM) were used to enhance granulation during the treatment of phenolic wastewaters in UASB reactors. Use of CaSO4, CaSO4 /GG, and CaSO4 /CPAM increased formation of granules (>0.25 mm) by 7%, 21% and 40%, respectively, after 90 days in comparison with the control. Use of CaSO4 /GG and CaSO4 /CPAM at an organic loading rate of 2.89 kg chemical oxygen demand (COD) m −3  d −1 increased the COD removal efficiency by 9% and 3%, respectively, in comparison with the control (75%). The CaSO4 enhanced the granulation rate as nuclei and the subsequent dissolution of CaSO4 improves the activity of methanogens. Polymers facilitated bacteria adhesion and improved the diversity of phenols-degrading bacteria. This study describes a new method for rapid granulation in UASB reactors when treating toxic and refractory wastewaters.